2012
DOI: 10.3109/03014460.2012.728621
|View full text |Cite
|
Sign up to set email alerts
|

Sibling composition and children's anthropometric indicators of nutritional status: Evidence from native Amazonians in Bolivia

Abstract: Older brothers and younger sisters were negatively associated with arm measures in girls. This finding may help improve policy interventions that aim to address children's nutritional health and long-term well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 77 publications
2
9
0
Order By: Relevance
“…Thus, our findings help bridge existing gaps in this literature by showing that children were viewed as healthier and had better anthropometric indicators of long-term (WFH, BMI) and shorter-term (SFT) energetic status when their fathers were ranked highly on direct care. In our sample, Bondongo children's energetic status (SFT, BMI) was qualitatively similar to findings from other resource-constrained, subsistence-level societies in which energy shortfalls and growth stunting are common (e.g., Houck et al 2013;Magvanjav et al 2013). Given the ecological and energetic conditions, our results are relevant to applied and evolutionary-oriented perspectives on fathers' effects on children.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Thus, our findings help bridge existing gaps in this literature by showing that children were viewed as healthier and had better anthropometric indicators of long-term (WFH, BMI) and shorter-term (SFT) energetic status when their fathers were ranked highly on direct care. In our sample, Bondongo children's energetic status (SFT, BMI) was qualitatively similar to findings from other resource-constrained, subsistence-level societies in which energy shortfalls and growth stunting are common (e.g., Houck et al 2013;Magvanjav et al 2013). Given the ecological and energetic conditions, our results are relevant to applied and evolutionary-oriented perspectives on fathers' effects on children.…”
Section: Discussionsupporting
confidence: 73%
“…Men's status as hard workers did positively predict higher SFT and WFH in their children, although the latter was not statistically significant and the former became nonsignificant after controlling for other factors, such as biological relatedness. Prior work has shown that fathers preferentially provision biological children (Anderson, Kaplan, and Lancaster 1999;Flinn 1988;Marlowe 1999), and nutritional benefits of provisioning would have differential effects on children of different ages, as growth, development, and activity demands change across childhood and adolescence (e.g., Magvanjav et al 2013). A primary limitation of our study was lack of power to examine the possible mediating or moderating effects of these demographic and household variables on the relationship between men's quality as providers and their children's health.…”
Section: Discussionmentioning
confidence: 94%
“…Market exposure and modernization have improved individual well-being, as indicated by significant increases in the monetary value of household food consumption (+6.3%/year) and in adult body mass indices (BMI; 0.7%/year) (Godoy et al, 2009); however, the forces of modernization have put increasing pressure on animal wildlife as increases in household wealth are positively associated with the consumption of forest animals (Godoy et al, 2010b). Our findings also suggest that households are resource constrained, as evidenced by the fact that children with more siblings had poorer anthropometric indicators of nutritional status (Magvanjav et al, 2013). For example, among girls, an additional older brother in the household was associated with a 4% decline in arm muscle area (p < 0.01), while an additional younger sister was associated with a 6% decrease in the triceps skinfold measures (p < 0.01).…”
Section: Findings: Substantive and Methodologicalmentioning
confidence: 60%
“…The presence of older siblings, with some exceptions (e.g., Hagen and Barrett, 2009), are generally associated with higher maternal fertility and improved child outcomes (Turke, 1988;Sear et al, 2000Sear et al, , 2002Crognier et al, 2001Crognier et al, , 2002Kramer, 2005). In contrast, younger siblings are associated with increased child mortality among the Dogon (Strassman and Gillespie, 2002) and reduced muscle and fat composition for Tsimane girls (Magvanjav et al, 2013).…”
Section: Human Cooperative Breedingmentioning
confidence: 99%